The Literary Contest for Promoting Writing (Journal of Parents and Teachers, 2025)
Organizing a literary contest in a school setting can be a very good initiative for students' cognitive and skill-based learning. But beyond that, it can become a transformative experience in the emotional learning of some students, one that accompanies them throughout their development and stays with them throughout their lives.
Keywords: creativity; writing; school activities; literature; reading